PRESUPOSISI DALAM PERCAKAPAN ANTAR TOKOH NOVEL KEMBANG TURI KARYA BUDI SARDJONO - Setiawan, Dwi; Salem, Laurensius; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: Pragmatics as one of the branches of the study of linguistics or linguistics has an important role in understanding the meaning of language. Because pragmatics relate the speech spoken by the participant to speak in the context of the situation, place, and time. Because of that pragmatics are needed in everyday conversation. One of the pragmatic branches is presupposition or presupposition. Presuppositions or presuppositions in conversations function to identify hidden information in a speech. Presuppositions consist of factual, non-active, lexical, structural, non-factive, and counterfactual presuppositions. Serves to examine the deeper meaning of speech from speech partners so that hidden information is obtained from speech. Presuppositions can be found in conversations between participants in the conversation. The novel is a literary work that uses conversation as a driver of the storyline that has many conversations. In the conversation, of course, a variety of information will be discovered by speakers to the speech partners. From these utterances, not all utterances will contain presuppositions. So it needs an in-depth analysis in accordance with the theory of presuppositions to determine whether the speech contains presuppositions or not. Â Keywords: presuppositions, conversations, participants, information